STUDI AKAR KEMISKINAN NELAYAN DI KELURAHAN BAIYA KECAMATAN TAWAELI KOTA PALU - Tahawila, Amrin (Katalogis, 2014)
Coastal area Society mostly is fisherman society, identik with the poorness. condition offisherman Life in Chief of village Baiya from first to date still in a state of which enough concern because can only fulfill the its life requirement everyday. The problem in this study were (1) how the condition of poverty in Sub Baiya fishing communities; (2) What level of depth (P1) and severity of poverty (P2) fishing communities in Sub Baiya. The theory used is the root of poverty theory, fishermen, poverty, poor, poverty fishermen, social systems, economic and social life. The method used is descriptive method . The data used for the research needs in the form of data: a) primary, ie, data that reveal the reality of the roots of poverty fishermen, (b) secondary data in the form of tables and pictures that have something to do with the object of research. The population of this research is fisherman society in chief of village Baiya, amounting to 133 people and sampel specified passing by technique of purpossive sampling namely by specifying 30 people according to specific characteristic owned. The results showed that the condition of the fishermen in the village Baiya still as poor as most are still using traditional equipment such as canoes, paddles , and nets . Second job is labor and services . The number of hours worked on average ranges between 7-8 hours per day. Average savings are not memeiliki ; income is only around Rp. 800.000,00 per month to Rp . 2,200,000.00 600,000 with the lowest spending levels ,and the highest spending levels Rp.1.500.000,00.  Characteristics  of  poverty  in  fishing  communities  characterized  by  poverty natural object of study, namely poverty created by the natural conditions that are particularly vulnerable to the attitude of a person or community members in improving their standard of living . Structural poverty is poverty caused by human factors such as economic policy and the unfair distribution of production assets are not evenly distributed. Poverty is the cultural attitudes of fishermen caused by lifestyle , habits , customs and traditions. Poverty levels are still below the poverty line fishers because of the ability of family income family members have not been able to prosper . While the severity of poverty fishermen indicate that the distance between the poor and the poverty line there is an imbalance because there is still a fishing community is still far away from the poverty line and some are otherwise .